2012
DOI: 10.1016/j.bjmsu.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Botulinum Toxin for Overactive Bladder Syndrome without Detrusor Overactivity

Abstract: Objective: To report our experience of intravesical botulinum toxin for idiopathic overactive bladder syndrome (OAB) without detrusor overactivity (DOA) on urodynamic assessment. Patients and methods: Data regarding presentation, diagnosis, urodynamic findings, date and dose of treatment, and outcomes were recorded prospectively for 94 patients undergoing intravesical botulinum toxin injection for idiopathic overactive bladder syndrome at our institution. The cohort included 19 patients without DOA on urodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Most, but not all, patients had evidence of detrusor overactivity (DOA) on urodynamic studies. A previous study showed that the presence of DOA on a urodynamic study did not influence the response to botulinum toxin type A treatment .…”
Section: Methodsmentioning
confidence: 92%
“…Most, but not all, patients had evidence of detrusor overactivity (DOA) on urodynamic studies. A previous study showed that the presence of DOA on a urodynamic study did not influence the response to botulinum toxin type A treatment .…”
Section: Methodsmentioning
confidence: 92%